INCREASING PROTECTION AGAINST UNAUTHORIZED ACCESS DURING VOTING IN STATE AUTHORITIES BASED ON HARDWARE BIOMETRIC IDENTIFICATION OF THE VOTER - PAVLOVSKIY, PAVLO; PRUSIAZHNYI, DMITRO; ABRAMCHYK, IGOR; SAVRATSKIY, V.; BILOUS, V. (Herald of Khmelnytskyi National University. Technical sciences, 2023)
A device is proposed to provide protection against unauthorized access to information based on the use of user authentication with the possibility of delimiting access to the information environment. The device allows early detection of unauthorized access attempts and provides access to information resources to authorized users; has increased durability and resistance to physical breaking, increases the security of the information protection system; is simple for the user and does not require special knowledge in the field of technical information protection; and also allows early detection of unauthorized access attempts, recovery of basic device functions in emergency situations and has a much lower price compared to analogues.